Qualitative assessment of precocious puberty-related user-created contents on YouTube - Hyo-Kyoung Nam; Soo Min Bang; Young Jun Rhie; Sang Hee Park; Kee-Hyoung Lee (Korean Society of Pediatric Endocrinology, 2015)
PurposeUser-created content (UCC) has provided a considerable amount of medical information and become an important source. We aimed to evaluate the quality and scientific accuracy of precocious puberty-related UCC on YouTube.MethodsThe keywords "precocious puberty", "early puberty", "sexual precocity", and "precocity" were searched for on YouTube during June and July 2014. More than 1,500 UCC matched the keywords. According to the information provider, UCC was classified as medical, oriental, or commercial & others. We evaluated the quality and scientific accuracy of the information provided in UCC using the DISCERN instrument and information scores, respectively.ResultsWe selected 51 UCC, which were categorized into three types: medical (n=17), oriental (n=17), or commercial & others (n=17). The overall quality score for medical UCC (3.4) was significantly higher relative to those of oriental and commercial & others UCC (2.8 and 2.3, respectively) (P<0.001). In the assessment of scientific accuracy, the mean information score for medical UCC (30.7) was significantly higher than those of oriental and commercial & others UCC (15.9 and 5.1, respectively) (P<0.001). The mean duration of oriental UCC was the longest (P<0.001), however, it was viewed less frequently among them (P=0.086).ConclusionThe quality and accuracy of precocious puberty-related health information in UCC were variable and often unreliable. The overall quality of UCC regarding precocious puberty was moderate. Only medical UCC provided scientifically accurate information. As UCC becomes a popular source of health information, it is important to provide reliable, scientifically accurate information.